Gender Stereotypes in the Workplace: Exploring Perceptions and Realities - Dr. Sabeen Ghayyur (Review Journal of Social Psychology & Social Works, 2023)
Gender stereotypes, ingrained expectations about how men and women should behave and perform in the workplace, continue to pervade professional environments despite significant strides towards gender equality. This article explores the multifaceted nature of gender stereotypes, their impact on individual experiences and organizational dynamics, and the persistent challenges they pose to achieving true workplace equality. We delve into research findings from social psychology, organizational behavior, and feminist studies, examining how these preconceived notions manifest in various forms of discrimination, from subtle biases in hiring and promotion decisions to overt gender-based harassment and microaggressions. By analyzing the interplay between individual perceptions, organizational cultures, and broader societal norms, the article aims to unpack the complex realities of gender stereotypes and propose strategies for dismantling their harmful effects on women's professional lives and fostering a more inclusive and equitable workplace for all.